2016
DOI: 10.1063/1.4961051
|View full text |Cite
|
Sign up to set email alerts
|

Infrared dielectric function of polydimethylsiloxane and selective emission behavior

Abstract: The complex refractive index of polydimethylsiloxane (PDMS) is determined in the wavelength range between 2.5 μm and 16.7 μm. The parameters of a Drude-Lorentz oscillator model (with 15 oscillators) are extracted from Fourier transform infrared spectroscopy reflectance measurements made on both bulk PDMS and thin films of PDMS deposited on the gold coated silicon substrates. It is shown that thin films of PDMS atop gold exhibit selective emission in the 8 μm to 13 μm atmospheric transmittance window, which dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 32 publications
0
43
0
Order By: Relevance
“…PDMS is a promising inexpensive material for daytime radiative cooling due to its transparency in visible regime and strong thermal emissivity in the mid-infrared regime. 39 Here we propose a simple planar PDMS/metal (Al or Ag) film structure to realize an inexpensive thermal emitter for radiative cooling, as illustrated in Fig. 1A.…”
Section: Designing the Planar Pdms Coated Metal Thermal Emittermentioning
confidence: 99%
“…PDMS is a promising inexpensive material for daytime radiative cooling due to its transparency in visible regime and strong thermal emissivity in the mid-infrared regime. 39 Here we propose a simple planar PDMS/metal (Al or Ag) film structure to realize an inexpensive thermal emitter for radiative cooling, as illustrated in Fig. 1A.…”
Section: Designing the Planar Pdms Coated Metal Thermal Emittermentioning
confidence: 99%
“…It was attributed to the hierarchical porous structure leading to a gradual refractive index transition from the polymer matrix to air cavities, [28] as well as the strong inherent absorption performance of PDMS in the wavelengths localized in LWIR window ( Figure S14, Supporting Information). [35] Because the water droplets in the emulsion were quite stable, the cavity distribution could be easily controlled by simply mixing the emulsion for different durations, allowing us to prepare samples with hierarchical cavity structure to optimize reflection performance (Figure 3a). In addition, the reflection of SPDMS film increases when the film thickness was increased from 300 to 500 µm but not from 500 to 600 µm ( Figure S15, Supporting Information).…”
Section: Doi: 101002/adma202000870mentioning
confidence: 99%
“…They showed that PDMS can act as a viable material for passive radiative cooling engineering applications. The measurement setup is shown in Figure 7 b [ 48 ]. Lee et al conducted the analysis of high temperature absorber with a structure of a 2D nickel grating atop a thin SiO film and a nickel substrate, as shown in Figure 7 c, they determined the size of the 2D grating with the Taguchi method optimizing the spectral absorptance in both S and P polarizations [ 49 ].…”
Section: Diverse Structures Of Metamaterialsmentioning
confidence: 99%